The Impact of COVID-19 on the Economy of Pakistan: A Trend Analysis on Macroeconomic Indicators and Political Situation - Qurat Ul Ain; Atteq Ur Rehman; Maryam Ali; Palwasha Khalil (Social Science Review Archives, 2025)
The COVID-19 pandemic reshaped economies worldwide, and Pakistan felt its impact across every primary sector. This study examines how the pandemic affected Pakistan’s economy, focusing on key indicators like growth, unemployment, poverty, exports, and imports. Using trend analysis and drawing from secondary data covering the years 2000 to 2023, we explore how these indicators shifted during the pandemic compared to the years before. The results show that 2020 was a particularly tough year, with economic activity slowing down sharply due to lockdowns and uncertainty. While recovery efforts in the following years brought some stability, the bounce-back was unequal across all sectors. Many people lost their jobs, especially daily wage workers and those in the informal economy, while poverty levels climbed, hitting vulnerable communities the hardest. International trade also hit, as global demand dropped and supply chains broke down. Alongside these economic challenges, the study also examines how political factors played a role. Political instability and inconsistent decision-making made it harder to respond effectively to the crisis. Overall, the study highlights the need for stronger, more inclusive policies that can help protect both the economy and the people during future crises. It offers practical insights for policymakers and others working to build a more resilient and fair economic future for Pakistan.